Aspects of mathematics instruction and education policy in Lithuania - Norvaiša, Rimas (Lietuvos matematikos rinkinys, 2022)
High-quality mathematics instruction for all means high expectations and strong support for all students. An insightful math teaching policy when apdating both school math curriculum and assessment system as well as  mathematics teacher training and in-service training program are required to implement this provision. This policy should be based on international mathematics education reserach. How realistic is it to implement in  Lithuania? From that point on, we will take mathematics teaching seriously depends on society's readiness for existing and future challenges.
Keywords: mathematics education policy; high-quality mathematics instruction for all; mathematics curriculum; assessing mathematical proficiency; qualification of a teacher; research in school mathematics